2017
DOI: 10.1002/jmr.2610
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and force probing of primary murine liver sinusoidal endothelial cells

Abstract: Liver sinusoidal endothelial cells (LSECs) represent unique type of endothelial cells featured by their characteristic morphology, ie, lack of a basement membrane and presence of fenestrations-transmembrane pores acting as a dynamic filter between the vascular space and the liver parenchyma. Delicate structure of LSECs membrane combined with a submicron size of fenestrations hinders their visualization in live cells. In this work, we apply atomic force microscopy contact mode to characterize fenestrations in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Our recent work demonstrated that even better insight into the dynamics of the fenestra structure could be achieved using multimodal AFM imaging. Dynamically tracking the detailed structure and dynamics of the fenestrae in vitro for the first time in living (ie, nonfixed) LSECs, enabled us to obtain time‐dependent high‐resolution images of the actin cytoskeleton that supports the fenestrae, confirming the previously reported fenestrae‐associated cytoskeletal structures . We showed that some FACRs are closed, that is, filled with lipid membrane, while others are open .…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our recent work demonstrated that even better insight into the dynamics of the fenestra structure could be achieved using multimodal AFM imaging. Dynamically tracking the detailed structure and dynamics of the fenestrae in vitro for the first time in living (ie, nonfixed) LSECs, enabled us to obtain time‐dependent high‐resolution images of the actin cytoskeleton that supports the fenestrae, confirming the previously reported fenestrae‐associated cytoskeletal structures . We showed that some FACRs are closed, that is, filled with lipid membrane, while others are open .…”
Section: Introductionsupporting
confidence: 84%
“…Because of the decreased stiffness (ie, relatively low Young's modulus) of living LSECs after CB treatment (see Figure ), we were unable to trace FACRs in real time . To further investigate the interconnection between actin and spectrin, we performed high‐resolution AFM imaging on fixed LSECs.…”
Section: Resultsmentioning
confidence: 99%
“…A virtual issue appeared in the Journal of Molecular Recognition in 2017 . Nine research articles composed this special issue . At the end of the conference, it was announced that the next one will be organized in Kraków, in 2017.…”
Section: Afmbiomed Conferencesmentioning
confidence: 99%
“…Although significant progress has been made on the structural and functional aspects of fenestrae since their original description in liver sinusoidal endothelial cells (LSECs), dynamic observations of life cells on a time‐lapse basis have been lacking until now. Over the past months, major breakthroughs on fenestra biology by Zapotoczny and colleagues have been reported by employing atomic force microscopy (AFM), providing liver sinusoidal cell biologists with the first glimpse of the increase versus decrease in fenestrae number under live‐cell imaging conditions in vitro (Fig. ).…”
mentioning
confidence: 99%
“…In conclusion, this novel experimental AFM design reported by Zapotoczny et al should be considered as a future benchmark to study intact LSEC fenestra dynamics. One can foresee, when combined with multiarray AFM cantilevers and correlated imaging approaches, that high‐throughput screening of various bioactive substances will be in reach shortly. In support, the team of Zapotoczny succeeded in establishing a workflow that enables the automated quantification of fenestra size and number in a statistically rigorous manner .…”
mentioning
confidence: 99%